Petronas’ upstream management model - Hoang Thi Dao; Nguyen Thu Ha (Petrovietnam Journal, 2020)
The article introduces the upstream management model of Petroliam Nasional Berhad (Petronas), experience in state management of oil and gas activities and experience in organisation and management of production and business activities, and compare the organization and management models of Petronas and the Vietnam Oil and Gas Group (Petrovietnam). Recommendations are then made on measures to improve the efficiency of the organisation and management of upstream activities in the new context.